TINJAUAN YURIDIS TERHADAP PENERBITAN SURAT PERINTAH PENYIDIKAN LEBIH DARI SATU KALI DALAM HUKUM ACARA PIDANA DI INDONESIA - Mulki Muhammad; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The issuance of the order to investigate more than once in the criminal procedural law in Indonesia is the background of the study. The Criminal Procedure Code as the basis for proceedings in the criminal justice system in Indonesia does not explain the issuance of investigation orders more than once. The Criminal Procedure Code only allows one to submit a pretrial to the status of the determination of him so that the law enforcement process is protracted and legal certainty is not carried out.As for the purpose of this study, first to find out the implementation on the issuance of a warrant for investigation more than once in criminal procedural law in Indonesian. Second to find out the ideal concept of issuing of a warrant for investigation more than once in criminal procedural law in Indonesian. This type of research is normative law, which examines legal principles against a legal event. This research is descriptive, that is research that seeks to provide systematic and careful facts with the characteristics of a particular population.From the results of the research, there are two things that can be concluded, first, how the implementation of the issuance of a warrant for investigation is more than once in criminal procedural law in Indonesia. Second, how is the ideal concept of issuing an order of investigation more than once in criminal procedural law in Indonesian.Keywords: Investigation Order - Criminal Procedure Code